Knowledge, responsibility and culture: food for thought on science communication (Italian original version) - Giancarlo Quaranta (JCOM: Journal of Science Communication, 2007)
The past few decades have been marked by a rapid scientific and technological development. One of the most paradoxical, and perhaps more disturbing, features of this process is the growing divide between the increased importance science has acquired in economic and social life and a society persistently showing spreading signs of contempt, mistrust and, most of all, disinterest in research.